2012
DOI: 10.1103/physreve.86.041308
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of granular jets: Is granular flow really a perfect fluid?

Abstract: We perform three-dimensional simulations of the impact of a granular jet for both frictional and frictionless grains. Small shear stress observed in the experiment [X. Cheng et al., Phys. Rev. Lett. 99, 188001 (2007)] is reproduced through our simulation. However, the fluid state after the impact is far from a perfect fluid, and thus the similarity between granular jets and quark gluon plasma is superficial because the observed viscosity is finite and its value is consistent with the prediction of the kinetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
6
29
1
Order By: Relevance
“…Here, we report that the shear viscosity consistent with our previous results, except its density dependence, and the assumption of the zero yield stress would be natural, by performing threedimensional simulation [9].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Here, we report that the shear viscosity consistent with our previous results, except its density dependence, and the assumption of the zero yield stress would be natural, by performing threedimensional simulation [9].…”
Section: Introductionsupporting
confidence: 73%
“…Thus, the correspondence between granular flow and QGP would be superficial [9]. However, through this analysis, zero yield stress, which is the residual stress without deformation, is assumed, though we presented three indirect evidences to support the assumption.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The viscosity of the granular fluid, however, obtained from the Couette flow is much larger than that obtained from the drag experiment. Indeed, an experiment for a granular jet (Cheng et al 2007) as well as simulations (Ellowitz et al 2013;Müller et al 2014) suggested that the granular fluid can be approximately represented by a perfect fluid, though there exist counter arguments (Sano and Hayakawa 2012;Sano and Hayakawa 2013). Therefore, another purpose of this paper is to resolve the current confusing situation on the rheology of granular fluids.…”
Section: Introductionmentioning
confidence: 94%
“…In spite of 16 orders of magnitude difference in their energy scales, the two examples share one common feature: they both illustrate emergent hydrodynamic flows out of strongly interacting discrete particles. Thus, granular jet impact has been studied in part as a macroscopic analog of the RHIC experiment [5,10,11] or as a fluid with a finite viscosity [12,13]. Indeed, similar to the anisotropic ejecta pattern of the quark-gluon plasma, an asymmetric granular sheet was produced in an experiment using a granular jet with a rectangular cross-section [5].…”
Section: Introductionmentioning
confidence: 99%